Aspek Hukum dalam Pemberdayaan Kelompok Wanita Pesisir Cungkeng dalam Rangka Peningkatan Penjualan Produk Serta Daya Saing di Kota Bandar Lampung - Aprinisa Aprinisa; Okta Ainita (LPPM Universitas Ekasakti Padang, 2023)
This research was motivated by the absence of legal aspects in order to increase product sales on the Cungkeng Coast, Bandar Lampung City. This research aims to explain the legal aspects of empowering the Cungkeng Coastal Women's Group in order to increase product sales and competitiveness in the city of Bandar Lampung. The method used in this research is a qualitative research method with a field study approach. Data collection techniques using field studies and literature studies. The collected data is processed and analyzed and conclusions are drawn. The results of this research explain that 1) The strategy for increasing capacity through legal aspects in improving processed squid cracker products on the Cungkeng coast includes maintaining product quality, increasing the strength of product branding, improving product quality and providing product guarantees if the product is damaged or unsuitable, and 2 ) Legal aspects in order to increase product sales on the Cungkeng Coast, Bandar Lampung City through several important aspects, including having a business registration number, distribution permit and halal regulations so that coastal nona squid cracker products on the Cungkeng Coast can be better known and trusted by the public.